2015
DOI: 10.1007/s11284-015-1243-9
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of hydrologic modifications to riparian plant communities in a large river system in northern China

Abstract: Hydrologic modifications to rivers caused by anthropogenic activity have major impacts on riparian ecosystems. Alterations to the hydrologic regime and their interactions with natural environmental parameters exert selective pressures on riparian vegetation, resulting in adaptations to specific flow attributes. However, few studies have attempted to detect these effects under multiple hydrologic conditions, especially for rivers in semi-dry and semi-humid regions. Using the ''space-for-time substitution'' meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Redundancy analysis (RDA) results showed that soil moisture strongly influenced the species hydrophilic types. Hydrophilicity of plants is the most direct manifestation of their adaptation to the environment [26]. Generally, hydric and mesic species have certain flood resistance abilities, with the majority having both vegetative propagation and seed reproduction capabilities, enabling them to quickly germinate after flood events [27].…”
Section: Discussionmentioning
confidence: 99%
“…Redundancy analysis (RDA) results showed that soil moisture strongly influenced the species hydrophilic types. Hydrophilicity of plants is the most direct manifestation of their adaptation to the environment [26]. Generally, hydric and mesic species have certain flood resistance abilities, with the majority having both vegetative propagation and seed reproduction capabilities, enabling them to quickly germinate after flood events [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, multi‐taxa models are rarely applied to plant research (but see Chen, Kery, Plattner, Ma, & Gardner, ) and default methods of determining community patterns include modelling community summary metrics (e.g. Laine, Kettenring, & Roper, ; Xiu, Gerisch, Ilg, Henle, & Ouyang, ) or multivariate techniques such as non‐metric multidimensional scaling (e.g. Hough‐Snee, Roper, Wheaton, & Lokteff, ) or detrended correspondence analysis (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Hough‐Snee, Roper, Wheaton, & Lokteff, ) or detrended correspondence analysis (e.g. Xiu et al., ). Although most of our metrics capture general community patterns fairly well, we see the additional taxa‐specific information and the predictive capabilities of our modelling technique as a substantial advantage when attempting to inform plant community management.…”
Section: Discussionmentioning
confidence: 99%
“…Flooding shapes the fluvial landforms and habitat gradients for the establishment and development of riparian vegetation [1][2][3][4][5]. Consequently, the flow regime is critical in the formation of plant communities [6][7][8][9][10], seed banks [11][12][13] and nutrient dynamics [14][15][16][17][18]. Riparian vegetation consistently adjusts to flood disturbances and sedimentation process (erosion and deposition of sediments) driven by the flooding history to maintain a dynamic equilibrium, with new conditions correlated with the elevation relative to the river water level [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%